Compensation, Role Conflict, and Work Stress on Turnover Intention: The Mediating Role of Work Engagement - Ary Triswanto; Agusta Dian Ellina; Prima Dewi Kusumawati (Innovative Approaches in Health Science Journal, 2026)
Background: Employee turnover can disrupt hospital staffing and service continuity. This study examined whether work engagement mediated the associations of compensation, role conflict, and work stress with turnover intention among employees of Toeloengredjo Hospital, Kediri. Methods: A cross-sectional survey included 159 of 265 permanent employees selected by simple random sampling. Five constructs were measured with self-report questionnaires. Pearson correlations and path analysis were conducted in Stata. Indirect effects were products of coefficients and tested using an approximate first-order delta method. Results: Compensation (b = 0.150, p = 0.049) and work stress (b = 0.146, p = 0.017) were positively associated with engagement; role conflict was not (p = 0.277). Role conflict (b = 0.176, p = 0.001) and engagement (b = 0.687, p < 0.001) were positively associated with turnover intention. The approximate indirect effect was supported for work stress (0.100, 95% CI 0.017 to 0.184, p = 0.019), but not compensation (p = 0.052) or role conflict (p = 0.277). Conclusion: The work stress pathway was indirect-only, but the positive engagement-turnover path contradicts theory and requires verification of item scoring. Cross-sectional data do not establish causal mediation.